PENGEMBANGAN BAHAN AJAR BERBASIS PERMAINAN PADA MATERI IPS SUMBER DAYA ALAM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH - Devi Fitriyani, - (2022)
Penelitian ini dilatarbelakangi oleh kelirunya siswa pada saat mengisi soal evaluasi materi IPS mengenai sumber daya alam. Kurangnya kemampuan berpikir kritis siswa dapat mempengaruhi hasil belajar siswa. Penggunaan sumber belajar pada saat proses pembelajaran hanya terfokus pada buku tema. Hal ini menyebabkan siswa jenuh dan perlu sumber belajar lain yang menarik bagi siswa. Penelitian ini bertujuan untuk mendeskripsikan pengembangan bahan ajar berbasis permainan pada materi IPS sumber daya alam untuk meningkatkan kemampuan berpikir kritis siswa kelas IV Sekolah Dasar. Penelitian ini menggunakan metode penelitian Desain and Development menurut Richey & Klein dengan menggunakan model PPE (Planning, Production, Evaluation). Partisipan dalam penelitian ini adalah validator ahli dan validator respon siswa untuk menilai kelayakan bahan ajar berbasis permainan. Validator ahli terdiri dari ahli materi, ahli media, dan ahli pembelajaran. Sedangkan validatos respon siswa terdiri dari dua orang siswa kelas IV. Hasil validasi para ahli mendapat rata-rata skor 90,2% dengan kategori "Sangat Layak". Sedangkan hasil validasi respon siswa mendapat rata-rata skor 91,3% dengan kategori "Sangat Layak". Kata kunci : bahan ajar berbasis permainan, sumber daya alam, Desain and Development, Planning, Production and Evaluation.  ABSTRACK DEVELOPMENT OF GAME-BASED TEACHING MATERIALS ON NATURAL RESOURCES OF SOCIAL RESOURCES MATERIALS TO IMPROVE CRITICAL THINKING SKILLS FOR CLASS IV ELEMENTARY STUDENTS This research was motivated by the students' mistakes when filling out the evaluation questions for social studies material regarding natural resources. Lack of students' critical thinking skills can affect student learning outcomes. The use of learning resources during the learning process only focuses on the theme book. This causes students to be bored and need other learning resources that are interesting for students. This study aims to describe the development of game-based teaching materials on natural resources social studies material to improve critical thinking skills of fourth grade elementary school students. This study uses the Design and Development research method according to Richey & Klein using the PPE (Planning, Production, Evaluation) model. Participants in this study were expert validators and student response validators to assess the feasibility of game-based teaching materials. Expert validators consist of matter experts, media experts, and learning experts. While the student response validatos consisted of two fourth grade students. The results of the validation of the experts got an average score of 90.2% in the "Very Feasible" category. While the results of the validation of student responses got an average score of 91.3% in the "Very Feasible " category. Keywords: game-based teaching materials, natural resources, Design and Development, Planning, Production and Evaluation.